Exercise prescription in patients with chronic obstructive pulmonary disease - Julian Alcazar; Carlos Rodriguez-Lopez; Ana Alfaro-Acha; Luis M. Alegre; Ignacio Ara Royo (Asociación Española de Ciencias del Deporte, 2018)
Chronic obstructive pulmonary disease (COPD) is characterized by persistent respiratory symptoms and airflow limitation. Apart from the ventilatory limitations, patients with COPD present an impaired exercise capacity that limits their ability to perform the activities of daily living and impact negatively on their quality of life. Limb muscle dysfunction is a systemic consequence of COPD associated with exercise intolerance, poor quality of life and increased mortality. This COPD-related syndrome is characterized by reduced muscle cross-sectional area, strength and endurance, and is highly prevalent among COPD patients. Thus, pulmonary rehabilitation (PR) is recommended in order to combat the negative consequences of COPD on patients' exercise capacity and quality of life. Exercise training is regarded as the cornerstone of PR and can be implemented at any stage of the disease. To date, the combination of resistance and endurance training (i.e. concurrent training) has demonstrated to be the most beneficial exercise intervention in COPD. Concurrent training provides clinically and statistically significant benefits in exercise tolerance and quality of life to patients with COPD. In addition, there are other potential adjuncts to exercise training and strategies to enhance the implementation of PR programs in COPD patients.